[tex]1\frac{1}{3}+2\frac{1}{3} = 3\frac{2}{3}\\\\\frac{4}{5}+1\frac{1}{5} = 1\frac{5}{5} = 2\\\\2\frac{4}{5}+\frac{3}{5} = 2\frac{7}{5} = 3\frac{2}{5}\\\\5\frac{3}{4}+3\frac{2}{4} = 8\frac{5}{4} = 9\frac{1}{4}\\\\\frac{7}{9}-\frac{3}{9} = \frac{4}{9}[/tex]
[tex]3\frac{1}{4}-2\frac{3}{4} = 2\frac{5}{4}-2\frac{3}{4} = \frac{2}{4} = \frac{1}{2}\\\\5-2\frac{1}{3} = 4\frac{3}{3}-2\frac{1}{3} = 2\frac{2}{3}\\\\5\frac{3}{7}-2\frac{3}{7} = 3\\\\6\frac{9}{13}-4\frac{12}{13} = 5\frac{22}{13} - 4\frac{12}{13} = 1\frac{10}{13}[/tex]